Virtual social support buffers stress response: An experimental comparison of real-life and virtual support prior to a social stressor. (June 2019) - Kothgassner, Oswald D.; Goreis, Andreas; Kafka, Johanna X.; Kaufmann, Marlene; Atteneder, Katharina; Beutl, Leon; Hennig-Fast, Kristina; Hlavacs, Helmut; Felnhofer, Anna
Abstract: Background and objectives: Face-to-face and text-based social support have been shown to attenuate stress responses in past studies. Yet as social interactions increasingly take place online by means of virtual humans, our objective was to examine whether different forms of social support (virtual vs. real) prior to the Trier Social Stress Test (TSST) would also decrease stress. Additionally, the effect on subsequent real-life social behaviors (helping and approach) was evaluated while controlling for affective states and social presence. Methods: 56 participants were either supported by an avatar, an agent, a real human or received no support before completing the TSST and two subsequent social behavior tasks (pen task and seating task). Results: Results show no difference in agency regarding social presence. Yet, participants with agent support and no support had significantly higher heart rates during the TSST and reported to be more worried. Also, they were more irritated and showed significantly slower helping reactions (picking up pens). Limitations: A limitation to this study is that only emotional verbal and non-verbal support were provided by a stranger. Different forms of support as well as a different source (i.e., a friend) may have a more pronounced effect on stress buffering. Conclusions: Virtual social support is as effective as face-to-face support in terms of stress buffering, as long as the recipient has the impression that it is provided by another human (via an avatar). This has wide ranging implications not only for health-related application in prevention and treatment but also for further research. Highlights: 1. Virtual social support is as effective as real support regarding stress buffering. 2. Virtual support has an effect on real-life behaviors like helping and approach. 3. Human controlled avatars are more effective supporters than computer agents. 4. Virtual social support may be used for prevention of stress related disorders.